2分之3+x-3分之2x+3=6分之3x+11
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/03 12:21:41
2分之3+x-3分之2x+3=6分之3x+112分之3+x-3分之2x+3=6分之3x+112分之3+x-3分之2x+3=6分之3x+11x-5=6X-103(2X+9)=5(3X+4)5X-11=1
2分之3+x-3分之2x+3=6分之3x+11
2分之3+x-3分之2x+3=6分之3x+11
2分之3+x-3分之2x+3=6分之3x+11
x-5=6X-10
3(2X+9)=5(3X+4)
5X-11=12分之X-5+13
1-4分之2X+1+3分之2X-1=12分X+1
要过程,谢谢了
2分之3+x-3分之2x+3=6分之3x+11
3/2+1/3x+3=1/2x+11
1/3x-1/2x=11-3-3/2
-1/6x=6.5
x=-39
6分之x-2=x分之x+3-1
(x+2)分之(x+1)-(x+7)分之1=(x+3)分之(x+2)-(x+6)分之1
3分之2x=12分之x平方+x平方分之3+x分之4
x-2-x分之3 分之 1+x分之6 +x^2分之5
2分之x+4-x+5=3分之x+3-6分之x-2
6分之X-9-3分之2+X=(x-1) -2分之X-2
解方程(:x-3分之x)+(x^2-3x分之x+6)=x分之x-3
(x-3)分之x+(x的2次方-3x)分之(x+6)=x分之(x-3)
(x²-4分之2x)-(x+2分之1)(x²-4分之2)+(x-2分之x)=1x分之3+x-1分之6=x(x-1)分之x-3
{x分之2-y分之3=4,x分之3+y分之6=5
X-3分之1=2+ 3-X分之X
2分之3-x>x-6分之7x-6
x²+x分之2+x²-x分之3=x平方-1分之4
5分之3x一7>=2分之x-2,4分之x一12分之2x一1>6分之1一3分之x
x-1分之x-1=x+2分之3
X+2分之X+3-X+4分之X+5=X+6分之X+7-X+8分之X+9,求X的值
x+1分之2x=1 x-2分之x-x^2-4分之1=1 x+3分之5=x分之2 x-2分之6=x+3分之x -1
5x分之6-2=x分之3